Sistem Rekomendasi Film Dengan Pendekatan Ontologi - Pratama, Qaris Ardian; Wibawa, I Gede Arta (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 12 No 2 (2023): JELIKU Volume 12 No 2, November 2023, 2023)
Movie is one of the easiest and cheapest entertainment human can experience. Nevertheless, there is an abundant amount of movies to watch. In the US and Canada alone, there are 403 movies produced in 2021. That is a huge amount of movies one person can watch. Most of people usually confused in determining which movies to watch, especially after watching a movie that truly suits their taste. Determining a decision in choosing a movie to watch requires a recommendation system. The recommendation system will provide decisions with good accuracy if it is collaborated with the Semantic Web using ontologies. In this study, researchers aims to build a movie ontology design which will later be used as a processing database in a movie selection recommendation system. In building the ontology, researcher requires the Methontology method. The methontology stages are performing the stages of specification, knowledge acquisition, conseptualizationo, integration, implementation, evaluation, and documentation.